Behavior of Centrifuged GFRP Poles Under Lateral Deflection - Youssef A. Awad; Ahmed M. EL-Fiky; Hosam M. Elhegazy; Mahmoud G. Hasan; Ibrahim A. Yousef; Ahmed M. Ebid; Mohamed A. Khalaf (Civil Engineering Journal, 2023)
Centrifugal-manufactured GFRP pipes are widely used today as lighting and low-power transmission poles due to their lightweight, high electrical insulation, low cost, and corrosion resistance. Despite these advantages, GFRP poles suffer high deflection problems due to their low elastic and shear moduli values. In order to overcome this disadvantage, three techniques were suggested to control the lateral deflection of the GFRP poles: an extended internal steel stub, external steel angles, and internal steel bracing bars. The main objective of this study is to determine the optimum strengthening technique to improve the serviceability of GFRP poles in terms of lateral deflection according to ASTM D4923. An experimental research program containing five full-scale GFRP poles was carried out to determine the optimum strengthening technique and the effect of connectors opening near the base and compare it to previous research. The results indicated that flexural stiffness was increased by 44%, 66%, and 38% for the extended stub, steel angles, and bracing bars, respectively. Besides that, the reduction in flexural stiffness due to connector opening was about 8%. The measured deflections showed good matching with simplified mathematical calculations, and the division was about ±10%. The external steel angle technique showed the best efficiency in Stiffness behavior. Doi: 10.28991/CEJ-2023-09-06-07 Full Text: PDF